Nomeando o inominável: a evolução das contribuições teóricas de Frances Tustin acerca do funcionamento dinâmico autístico em crianças e adultos - Ferreira, Juliana Araújo [UNESP] (2014)
Frances Tustin was a renowned child psychotherapist psychoanalytically oriented that, with her original conceptions and therapeutic effectiveness, expanded the existing theories on autistic processes influencing therapists in their clinical and academic work in many places around the world. We aim to fill a gap in the literature on the subject in Brazil which, currently, presents a fragmented view of the author´s work, resulting in a partial and a-historical understanding of her conceptual system. The objective of this work is to understand the historical evolution of the work of Frances Tustin in the original context in which it was produced. To this end, we developed a qualitative research, circumscribed in the field of psychoanalytic historiography, drawn from a historical-epistemological approach. This consists in a study of the major concepts of an author by reading and painstaking analysis of his work, taking into consideration various factors of influence, such as: the historical and psychoanalytical period, the author's biography, his clinical experience, among others. The research material was the complete writings of Frances Tustin. From a detailed review process the work was divided into three main periods: 1) Early Writings (1951-1972), where her initial thoughts where presented as the concept of normal and pathological infantile autism, psychotic depression and autistic processes, the first classification system and the first considerations about autistic etiology; 2) Elaborations (1973-1989), period in which the author expands and presents several original concepts on the dynamic functioning of these states such as autistic objects and autistic shapes, primitive terrors and autistic barriers in neurotic patients and 3) Revisions (1990-1994), when the author makes important revisions in her work and abandons ideas such as the existence of a period of normal autism in the development of ...